Modeling Of Vibration Transmission And Prediction Of Structure-Borne Noise In Buildings - Cheah, Yee Mun (2016)
Vibration originating from mechanical services are often the source of structure-borne noise in buildings. The transmitted vibration waves from the service equipment can propagate through the building structures and can eventually radiate sound which causes an audible low frequency noise causing disturbance inside the building. Models and discussions on of the vibration transmitted through the building structures are still lacking, particularly on how it is radiated as sound. This project proposes the development of firstly, a generic analytical model of a 2D portal frame structure consisting of column and beam elements. The results of the velocity of the structures are validated with those from Finite Element (FE) model.Bending waves in the building structure are presented through the operation deflection shapes diagram. Secondly, the 2D FE model is extended to a 3D FE model to include plate elements to represent walls, floors and roofs in a building. Using the hybrid FE/SEA analysis in VA One software, sound pressure level (SPL) in the building environment can be predicted using the injected power data of the motor obtained from the reception plate experiment. With the induction motor speed of 50 Hz, the overall SPL are 44 dB and 42 dB for the upper and lower cavities of the building respectively. These levels depend on the input power injected by the motor which is also directly affected by the mechanical faults in the motor i.e. mass unbalance and structural looseness. It is demonstrated that the SPL varies due to the faults in the motor. The result shows that the model can be applied as a preliminary predictive guide on the building design to minimize noise and vibration generated by service equipment.